Phylogeny of Mysis (Crustacea, Mysida): history of continental invasions inferred from molecular and morphological data - Audzijonyte, A; Damgaard, J; Varvio, S-L; Vainio, JK; Vainola, R (Cladistics, 2005)
We studied the phylogenetic history of opossum shrimps of the genus Mysis Latreille, 1802 (Crustacea: Mysida) using parsimony analyses of morphological characters, DNA sequence data from mitochondrial (16S, COI and CytB) and nuclear genes (ITS2, 18S), and eight allozyme loci. With these data we aimed to resolve a long-debated question of the origin of the non-marine (continental) taxa in the genus, i.e., glacial relicts in circumpolar postglacial lakes and arctic immigrants in the Caspian Sea. A simultaneous analysis of the data sets gave a single tree supporting monophyly of all continental species, as well as monophyly of the taxa from circumpolar lakes and from the Caspian Sea. A clade of three circumarctic marine species was sister group to the continental taxa, whereas Atlantic species had more distant relationships to the others. Small molecular differentiation among the morphologically diverse endemic species from the Caspian Sea suggested their recent speciation, while the phenotypically more uniform glacial relict species from circumpolar lakes ( Mysis relicta group) showed deep molecular divergences. For the length-variable ITS2 region both direct optimization and a priori alignment procedures gave similar topologies, although the former approach provided a better overall resolution. In terms of partitioned Bremer support (PBS), mitochondrial protein coding genes provided the largest contribution (83%) to the total tree resolution. This estimate however, appears to be partly spurious, due to the concerted inheritance of mitochondrial characters and probable cases of introgression or ancestral polymorphism.